Effectiveness Of Feedback, Reframe, Assess, Model, And Enhance (FRAME) in the Enhancing of Learners’ Performance of 9 Grader Students in Mathematics - Rudy D. Ebajan; Victoria D. Tamban (Research Synergy Foundation, 2024)
Despite great efforts by the Department of Education, the Philippines during the 2022–2023 period exhibits one of the narrowest disparities in arithmetic performance between students in the highest and lowest quartiles of the economic, social, and cultural status index. This insight motivates the current study’s goal of developing material that will help enhance the student's performance in mathematics. This study developed Strategic Intervention Material (SIM) to enhance the learners’ performance in mathematics among 9th graders of Don Jose Integrated High School in the City of Santa Rosa, Laguna. The SIM was designed to help the selected 62 participants learn geometry competency. A quasi-experimental research method was employed in this study to determine whether intervention materials improved mathematics learners’ performance. The analysis of pretest, formative test, and post-test performances in both the experimental and comparison groups provides a comprehensive look at the impact of educational interventions. Hence, there is a statistically significant difference between the pretest, formative, and post-test scores in enhancing learners’ mathematics performance with the use of strategic intervention material. The use of Strategic Intervention Material promotes active learning and engagement among learners; thus, it can be used to help students with mathematics anxiety. Results showed that SIM effectively enhances learners’ mathematics performance based on the mean, standard deviation, independent sample t-test, and Cohen’s d. Moreover, the subjects demonstrated positive behavior toward the intervention. This entails cutting down on improper behavior, spending more time on instruction, and assisting instructors in teaching, modeling, and meeting students’ needs.